1998
DOI: 10.1152/jappl.1998.84.2.717
|View full text |Cite
|
Sign up to set email alerts
|

Controlled dissolution from wax-coated aerosol particles in canine lungs

Abstract: Treatment of pulmonary and systemic diseases may be improved and toxicity reduced by pulmonary deposition of drug-containing aerosols exhibiting delayed dissolution. Aqueous disodium fluorescein and pentamidine aerosols were dried, concentrated, and condensation coated with paraffin wax. The apparent mass median aerodynamic diameters of the coated fluorescein particles were 2.8-4.0 microns. Wax-to-fluorescein ratios were 0.38-1.05. The dissolution half times determined using a single-pass flow system were 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…We found that nebulized fluorescein is rapidly absorbed in the bloodstream reaching a peak concentration approximately 20 min after initiating its administration, which is comparable to data from previous pharmacokinetic studies in experimental animals [9]. Fluorescein accumulation in visceral pleura was promptly visible after its administration, and its concentration followed a pattern similar to that in the blood, as assessed by fluorometric analysis (fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that nebulized fluorescein is rapidly absorbed in the bloodstream reaching a peak concentration approximately 20 min after initiating its administration, which is comparable to data from previous pharmacokinetic studies in experimental animals [9]. Fluorescein accumulation in visceral pleura was promptly visible after its administration, and its concentration followed a pattern similar to that in the blood, as assessed by fluorometric analysis (fig.…”
Section: Discussionsupporting
confidence: 87%
“…Aerosol administration of solid disodium fluorescein has been used in dogs to study the pulmonary and systemic deposition of drug-containing aerosols [5,6,7,8,9]. These studies showed that even a lipophobic compound such as fluorescein is absorbed rapidly via the lung when administered as an inhalation aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies suggested that the coated particles had longer retention time (significantly longer half-life) and slower release rate than the uncoated drug. Another method reported for coating from the vapor phase is condensation coating (248). Aqueous disodium fluorescein and pentamidine aerosols were dried, concentrated, and condensation Preparation of drug micro-and nanoparticles, also solid or porous composite particles for controlled release coated with paraffin wax.…”
Section: Particle Coatingmentioning
confidence: 99%
“…For effective deposition in the lower airways and deep lung, where drugs are most efficiently absorbed, the particle aerodynamic diameter (Dae) needs to be in the 1-5 μm range [4][5][6][7][8][9][10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%